CenPRIS AIMS TO BE PIONEER IN POLICY RESEARCH - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 19 March 2016 – The USM Centre for Policy Research and International Studies (CenPRIS) is aiming to be a reputable centre for policy research, not only in Malaysia but also throughout the world in many aspects of socioeconomy, social development, social issues and other matters that would be impactful to the future of the society.